Maternal Risk Factors of Delivering Low Birth Weight Infant at Choaprayayomraj Hospital - Haruehansavasin, Somchai (Journal of Health Science of Thailand, 2018)
Low birth weight (LBW) is a major public health problem. It increases evidence of newborns mortality and morbidity. Furthermore, it leads to developmental impairment of infant. To find out the risk factors of LBW delivery in Choaprayayomraj Hospital, a retrospective case-control study in mothers who delivered from 0ctober 1, 2007 to September 30, 2008 in Choaprayayomraj Hospital was carried out. Mothers who had > 28 weeks gestational age and live birth fetus were divided into two groups. The study group was 312 mothers who delivered newborns of < 2,500 gm and the control group was 2,609 mothers who delivered newborns of > 2,500 gm. Character of population were descripted wth number and percent. Variable data were analyzed with chi-square test at level of significant 0.05, odds ratio (OR) and 95% confidence interval (95%CI). It was found that maternal age < 20 or > 35 yrs, weight gain < 10 kg, 1st parity, gestational age < 37 weeks, 1st ANC > 12 weeks, ANC visit < 4 times, anemia (Hb < 11gm%), obstetric complication, history of LBW delivery, maternal behavior showed significant risks but body mass index < 20 kg/m2, medical complications did not. Reliability of risk factors were examined by multiple logistic regression analysis and risk effects on LBW delivery were ranked by adjusted OR, 95%CI. Only two risk factors were significantly reliable. The highest risks was gestational age < 37 weeks, ANC visit < 4 times, respectively. This result will contribute program development to decrease LBW delivery.